1996
DOI: 10.1063/1.471018
|View full text |Cite
|
Sign up to set email alerts
|

Crossover of the concentration dependence of swelling and elastic properties for polysiloxane networks crosslinked in solution

Abstract: We have investigated the preparation concentration dependence of the polymer volume fraction and the elastic modulus of the equilibrium swollen polydimethylsiloxane networks in toluene. The networks were prepared by the end-linking method in solution with a wide range of concentration. The network samples were attempted to be as small amount of structural defects as possible. The crossover has been observed for the preparation concentration dependence of the degree of equilibrium swelling and the elastic modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 57 publications
5
64
0
Order By: Relevance
“…; [13,43] while there were a few studies to report the crossover of the f m -dependence at f ÃÃ . Urayama et al [26] reported the crossover using the end-linked PDMS networks. This difference may be attributed to the difference of the network structure.…”
Section: Effect Of Swelling and Deswelling On The Mechanical Propertimentioning
confidence: 98%
“…; [13,43] while there were a few studies to report the crossover of the f m -dependence at f ÃÃ . Urayama et al [26] reported the crossover using the end-linked PDMS networks. This difference may be attributed to the difference of the network structure.…”
Section: Effect Of Swelling and Deswelling On The Mechanical Propertimentioning
confidence: 98%
“…If the network is crosslinked in bulk, entanglements are trapped whenever the PDMS chain length exceeds the entanglement molecular weight. On the other hand, in the system where PDMS is crosslinked in solution, the number of trapped entanglements is governed by the polymer concentration [24].…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, the PDMS networks are cured for 2 -3 days at 75°C [10,22,23]. Furthermore a few authors crosslink the networks in solution [8,9,15,[24][25][26][27]. If the network is crosslinked in bulk, entanglements are trapped whenever the PDMS chain length exceeds the entanglement molecular weight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trapped entanglements formed in the crosslinking stage are, however, not disentangled by swelling because the network topology is fixed upon crosslinking. In fact, several studies 16,17 have clearly revealed a significant contribution of the trapped entanglements to the small-strain modulus of fully swollen networks. On this basis, we simply expect the trapped entanglements to also contribute to a large-deformation behavior in the highly swollen state.…”
mentioning
confidence: 99%